Quince Powder Increases Antioxidant Activity and Probiotic Survival in Yoghurt - Şenay Burak Çınar; Gülfem Ünal; Gülşah Çalışkan Koç; Safiye Nur Dirim; Ayşe Sibel Akalın (Food Technology and Biotechnology)
Research background. In recent years, there has been a growing interest in incorporating fruit-based additives into yogurt formulations as a means to improve the functionality of the product. This study aims to produce a functional product by incorporating quince, which is rich in fibre, vitamins, minerals and antioxidant activity, into a yoghurt formulation. Experimental approach. The influence of the addition of quince powder (0 (control), 0.5, 1.0 and 1.5 %) on the antioxidant and proteolytic activities and culture viability of probiotic yoghurt was investigated for 28 days. Results and conclusions. The viable counts of yoghurt bacteria and Bifidobacterium lactis BB-12® were above 8 log CFU/g. Higher viability of all bacteria was obtained in yoghurt fortified with 1.5 % quince powder than those of other samples after 14 days. Probiotic yoghurt with added 1.5 % quince powder had the highest proteolytic activity during the last two weeks of storage, while the highest total phenolic content and (2,2-diphenyl-1-picrylhydrazyl) radical (DPPH˙) scavenging activity were obtained for the same sample throughout the storage period. Novelty and scientific contribution. Quince powder supports the health of the digestive system thanks to its high fibre content, while it is also rich in vitamins, minerals and antioxidant activity. These properties emphasise the importance of using quince powder in yoghurt production. This innovation has the potential to provide consumers with a tasty alternative, while at the same time increasing the intake of health-promoting ingredients. Furthermore, such products offer higher nutritional value than conventional yoghurt, offering consumers with a healthier option. Therefore, the production of yoghurt with quince powder can be considered as an important innovation in the field of nutrition and a practice that contributes to increasing health awareness.